Agro-based enterprises A way forward to women empowerment - Yadav, Seema; Dubey, S K; Singh, S K; Singh, Raghwendra (Indian Farming, 2024)
Women's contribution to agriculture is significant as they are the major food producers across the world. Though they perform more than 80% of the agricultural activities, their role and contribution in agriculture remain unrecognized and overlooked. Women farmers are identified as an imperative link in the development of agriculture and allied sectors (livestock production, fishing, horticulture, agroforestry, post-harvesting operations, etc.). Women farmers could increase farm yield by 20-30%, which could raise agricultural output in developing countries by 2.5-4%, if they had the same access to productive resources and training as men. Women constitute about 33% of cultivators and about 47% of agricultural labourers (MANAGE 2021). For adding more power to the agriculture sector, recognizing women and strengthening their status from farm to home is the need of the hour. Women empowerment through agro-based enterprise is an emerging solution for establishment of their powerful status and overall development of the society.